Supply chain logistics management - Bowerbox, Donald J.; Closs, David J.; Cooper, M. Bixby (Boston, 2007)
The book encompasses the development and fundamentals of the logistics discipline within a supply chain structure. It presents the vision of the future of business logistics and supply chain management and their role in enterprise competitiveness
Keywords: Business logistics